The Impact of Corporate Governance on Value Creation in Entrepreneurial Firms - Tan, Wee Liang (Institutional Knowledge at Singapore Management University, 2004)
The compliance with codes of corporate governance has become the norm for listed firms all over the world. In most countries, entrepreneurial firms do not have to comply with such codes but it has been argued that such codes should also apply to these small medium enterprises (SMEs). Since corporate governance forms the environment for the internal activities of a company and appropriate environmental conditions are crucial for corporate entrepreneurship to flourish in a company, it is apt that these two topics be discussed in relation with each other. Corporate governance mechanisms may dampen value creation in firms if appropriate measures are mandated by the regulators. This paper examines the implications of the extension of corporate governance principles to SMEs and the impact this will have on value creation through corporate entrepreneurship.